Negative interest rates - Sarkis Joseph Khoury; Poorna C. Pal (Journal of Risk and Financial Management, 2020)
Negative interest rates are an invention of monetary authorities to show that monetary activism does not have boundaries, i.e., as if there is no such thing as a liquidity trap. Their presence in the financial landscape has redefined the benefits to savers and to investors. Governments can now borrow at will without visibly adding to budget deficits. This makes negative interest borrowing an alternative to raising taxes. Banks can now achieve regulatory compliance partially at the expense of depositors. Commercial banks pay to keep money at the central bank instead of earning interest on it. This paper shows the true nature of negative interest rates and their consequences on various economic agents and performance measures, specifically on economic growth and exchange rates. In addition, this paper demonstrates that the arguments in favor of negative interest rates have been largely exaggerated based on the weight of the evidence that shows the United States, which never issued negative interest rates debt, is a leader among developed countries in terms of economic growth in a non-inflationary environment.
Keywords: 330; negative rates; nominal rates; exchange rates; monetary policy; fiscal policy; saving rates; budget deficits; economic growth